2013
DOI: 10.1007/s12928-013-0164-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome after endovascular treatment for isolated common femoral and popliteal artery disease

Abstract: The safety and patency of endovascular treatment (EVT) in isolated common femoral artery (CFA) and popliteal artery (PA) remain poorly understood. We investigated the efficacy after EVT for isolated CFA and PA disease. This study was performed as a multicenter retrospective registry of a prospectively maintained database. Between January 2001 and December 2010, consecutive 183 patients (214 lesions; CFA 111, PA 103) who received endovascular procedure for de novo isolated CFA and PA disease were enrolled. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 13 publications
3
62
0
Order By: Relevance
“…The methodological quality of the 28 case series was generally low ( Table S5 , supporting information). Only ten studies collected data prospectively, of which five reported endovascular intervention and five reported CFE. Less than half of the studies (11 of 28) had a sample size of greater than 100 and follow‐up of 1 year or more, of which four were in the endovascular group and seven were in the CFE group ( Table S6 , supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…The methodological quality of the 28 case series was generally low ( Table S5 , supporting information). Only ten studies collected data prospectively, of which five reported endovascular intervention and five reported CFE. Less than half of the studies (11 of 28) had a sample size of greater than 100 and follow‐up of 1 year or more, of which four were in the endovascular group and seven were in the CFE group ( Table S6 , supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…13 The reported 1-and 5-year restenosis rate of ET in the CFA is poor at 27.6% and 53.1%, respectively, especially when compared to the 9% restenosis rate reported for CFE at 5 years. 10,15,30 A high-technical failure rate of up to 10%, combined with worse durability than CFE could potentially lead to multiple interventions, even culminating in CFE, that may increase risk of periprocedural complications and escalate costs. 6,16 The CFE can still be considered as a safe and durable firstline treatment for CFA occlusive disease.…”
Section: Discussionmentioning
confidence: 99%
“…CLI patients often have multi-level arterial occlusive disease, especially below-the-knee occlusive disease. 18 Patients with tissue loss or gangrene should undergo complete revascularization to the ankle as permitted by the patient's condition, although patients with claudication or rest pain might undergo CFE alone. Although patients with CFA lesions and skipped SFA or below-the-knee lesions underwent CFE and combined procedures, the patients with complex lesions on CFA to SFA underwent CFE with a femoro-popliteal or femoro-tibial bypass.…”
Section: Kuma S Et Almentioning
confidence: 99%